Rare splenic complications and specific serology: decisive diagnostic tools in two cases of visceral leishmaniasis - Andrea Celestini; Federica Paglia; Orlando Dell’ Unto; Riccardo Guarisco; Claudio Puoti (Italian Journal of Medicine, 2012)
Introduction: Visceral leishmaniasis (VL) is a major endemic vector-borne disease in Southern Europe. We present two cases of VL, both characterized by splenic complications. Methods and results: Case 1: A 47-year-old female presented with effort angina, hepatosplenomegaly and pancytopenia. The clinical course was complicated by splenic infarction. Although bone marrow biopsy failed to show amastigotes, diagnosis was performed by a fast agglutinating screening test (FAST) and confirmed by a direct agglutinating test (DAT). The patient was treated successfully with AmBisome. Case 2: A 22-year-old male who had undergone a splenectomy to treat splenic rupture related to a minor trauma four months earlier presented with fever, nocturnal sweats and weight loss. The lack of pancytopenia was due to the absence of the spleen. The first biopsy did not identify parasites, but because the FAST had been positive, another bone marrow biopsy was performed, which demonstrated leishmaniasis. This patient was treated with the same schedule of AmBisome infusion. Discussion: 1) The clinical presentation of VL can be atypical, 2) splenic complications can characterize this disease, and 3) specific serology may be an important tool to reach a diagnosis.